How organizational constraints undermine sustainability actions in a university's campuses: A case study - Amaral, Ana Rita (2023)
Higher Education Institutions frequently struggle between the urgency to advance toward more sustainable campuses and the slow pace of their transformation. Although several stimuli and barriers are identified in the scientific literature, difficulties persist as several actions commonly assumed as best practices demonstrate to fall short of planned goals. Findings in the literature are generic, lacking the identification of concrete aspects which affect the effectiveness of strategies. This work contributes to filling this gap. Driven by the aim to understand this phenomenon in the University of Coimbra, a case study approach was adopted and a qualitative method was carried out with all key players to map the decision-making process and understand how strategies in the areas of energy and buildings on campus are implemented. Findings revealed the consequences of approaching sustainability through the implementation of isolated technical solutions without an integrated strategy or a sustainability-based institutional culture. Significant organizational constraints, such as the lack of internal cooperation and communication together with rigid procedures, undermine practices on campus energy and buildings operations, previously misconceived as financial or technical barriers. Despite the existence of literature discussing organizational barriers, the extent to which they may interfere with the technical performance of energy-efficient systems and buildings is a novel disclosure. By showing how unveiling specific problems that need to be overcome may support the construction of adequate internal policies, help decision-makers optimize sustainability actions, and encourage a better use of resources and know-how, this study’s approach and findings can provide useful insights to this and to other universities struggling with similar challenges. Thus, more case studies are recommended to compare outcomes at different levels – geographical, socio-economic, and technical – and contribute to comprehensive models for sustainable campuses.